Unsteady Ekman-Stokes dynamics: implications for surface-wave induced drift of floating marine litter - Higgins, C; Vanneste, J; van den Bremer, TS (American Geophysical Union, 2020)
We examine Stokes drift and wave‐induced transport of floating marine litter on the surface of a rotating ocean with a turbulent mixed layer. Due to Coriolis‐Stokes forcing and surface wave stress, a second‐order Eulerian‐mean flow forms, which must be added to the Stokes drift to obtain the correct wave‐induced Lagrangian velocity. We show that this wave‐driven Eulerian‐mean flow can be expressed as a convolution between the unsteady Stokes drift and an “Ekman‐Stokes kernel.” Using this convolution, we calculate the unsteady wave‐driven contribution to particle transport. We report significant differences in both direction and magnitude of transport when the Eulerian‐mean Ekman‐Stokes velocity is included.